Ulcus Vulvae Acutum Lipschütz—UVAL: case series at a Swiss university hospital emergency room - Guareschi, Vittoria; Mathevet, Patrice; Jacot-Guillarmod, Martine (Frontiers in Reproductive Health, 2024)
Background Ulcus Vulvae Acutum Lipschütz (UVAL) is a largely unknown disease with a broad and complex differential diagnosis. Objectives To provide a description of the main characteristics of UVAL, determine the most appropriate diagnostic process and describe the current therapeutic approach. Methods We designed a retrospective, descriptive cohort study using the gynecological-ER database of our institution. Inclusion criteria: female patients aged between 10 and 20 years old with suspicion of a UVAL diagnosis at CHUV's gynecological ER. Data extraction: epidemiological characteristics, clinical presentation, laboratory tests, established diagnostics, treatment, and ulcer outcomes. Results 15 patients were included for the analysis; average age: 15 years old; 60% of patients were virgo at the time of ulcer onset; all patients had at least one flu-like symptom concomitant with the vulvar lesion; the most-performed serology was for EBV and acute disease was present in only one patient; for diagnostic purposes two biopsies were performed with both inconclusive histopathology analysis; the main prescribed treatments were: oral NSAIDs, Paracetamol, and Lidocaine gel; 93% of cases presented signs of regression; the average follow-up time was 10 days. The diagnostic algorithm of Sadoghi et al: 10 out of 15 cases were retrospectively diagnosed with UVAL by the algorithm; half were diagnosed with UVAL, and the other half received a diagnosis of “ulcers of unknown origin” at the time of the gynecological ER visit. Conclusions We highly recommend the diagnostic and therapeutic algorithms developed by Sadoghi et al. as valuable tools to guide clinical reasoning and, consequently, improve acute vulvar ulcers management.